'Can you sleep tonight knowing that child is going to be safe?': Australian community organisation risk work in child protection practice. (17th August 2020) - Maslen, Sarah; Hamilton, Sharynne L.
ABSTRACT: Risk averse practice has dominated the child protection field for decades, with high-profile child deaths, ever-tightening surveillance, and regulation of families. In this context, the practice of social work as 'risk work' including the use of risk assessment tools has been subject to substantial scholarly investigation. Less attention has been paid to the community organisations that play a central role in supporting child protection-involved parents. Based on interviews with Australian community workers, we examine their negotiation of the parent support/parent risk dichotomy. From the perspective of community workers, the overly reductive, process-oriented risk judgements of child protection workers lead to both false positives and false negatives, with harmful impacts on the health and wellbeing of children and their families. Community workers resisted such approaches. Perceived failures of justice and care drove some to take liberties in their mandatory reporting obligations to guide outcomes. We argue that including the expertise of community workers in child protection assessments would better support child and family wellbeing.